2009
DOI: 10.1352/1934-9556-47.5.337
|View full text |Cite
|
Sign up to set email alerts
|

New Voices in Women's Health: Perceptions of Women With Intellectual and Developmental Disabilities

Abstract: This study explored aging and health experiences and concerns of women with intellectual and developmental disabilities, using a participatory approach that captured the direct reports of the women, in their own words and from their own perspectives. The results of a qualitative analysis of 6 focus groups, composed of 34 women with intellectual and developmental disabilities, Age 30 years and older are reported. The focus groups addressed health knowledge, body awareness,developmental and age-related changes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 13 publications
4
29
0
Order By: Relevance
“…One study using focus groups to explore the health of intellectually disabled women 14 reported that many women had stopped going for mammograms because their experiences were upsetting. For women of normal intelligence from ethnic minority groups, fear of the results, lack of insurance, trust in their physician, a sense of fatalism, and embarrassment about undergoing the test affected their likelihood of obtaining a mammogram.…”
Section: A M M O G R a Phy A Nd In T El L Ec T U A L Dis A Bil I T Iesmentioning
confidence: 99%
“…One study using focus groups to explore the health of intellectually disabled women 14 reported that many women had stopped going for mammograms because their experiences were upsetting. For women of normal intelligence from ethnic minority groups, fear of the results, lack of insurance, trust in their physician, a sense of fatalism, and embarrassment about undergoing the test affected their likelihood of obtaining a mammogram.…”
Section: A M M O G R a Phy A Nd In T El L Ec T U A L Dis A Bil I T Iesmentioning
confidence: 99%
“…Notably, among women with ID, the relative risk of death from breast cancer versus the relative risk of death from cervical cancer was 7:1, and sexual inactivity is a protective factor against cervical cancer, but nulliparity is a risk factor for breast cancer (Davies & Duff, 2001;Kelsey, Gammon, & John, 1993). Women with ID do not undergo mammography because the examination experience is upsetting (Brown & Gill, 2009). In addition, following the guidelines for mammography is difficult for women with ID; therefore, breast ultrasounds or clinical breast examination may be attempted as alternatives to resolve this problem (Sullivan et al, 2003) and achieve the objective of protecting women with ID.…”
Section: Discussionmentioning
confidence: 99%
“…Problems with communication or a lack of knowledge or understanding of a procedure may cause women with intellectual disability to not seek or be unable to seek appropriate care (Brown & Gill, 2009;Sullivan, Slack-Smith, & Hussain, 2004;Wilkinson, Deis, Bowen, &. Bokhour, 2011).…”
mentioning
confidence: 99%
“…51, No. 1,62-73 ©AAIDD DOI: 10.1352/1934 anxiety may stem from past trauma (Brown & Gill, 2009). In one study, 76% of responding nurses reported that cancer-screening exams could not be performed without some type of intervention because of the person with an intellectual disability's behavior or "lack of cooperation" (Tyler et al, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation